TaqI polymorphism of the VDR gene: aspects related to the clinical behavior of COVID-19 in Cuban patients - Estela Morales Peralta; Yaíma Zúñiga Rosales; Teresa Collazo Mesa; Elvia Nelmi Santos González; Yadira Hernández Pérez; María de los Ángeles González Torres; Hilda Roblejo Balbuena; Beatriz Marcheco Teruel (Egyptian Journal of Medical Human Genetics, 2021)
Abstract Purpose To determine the relationship between the genotypes of the TaqI polymorphism of VDR gene and the clinical forms of COVID-19 in Cuban patients. Methods TaqI polymorphism was determined by the PCR in 104 Cuban patients, who suffered different clinical forms of COVID-19. Results There was a greater possibility of presenting symptomatic forms [OR = 2.081, 95% CI: 0.243–17.842], even severe [OR = 1.200, 95% CI: 0.217–6.638], related to the tt genotype. Conclusion There are signs of association between the risk of developing COVID-19 and the genotypes of the TaqI polymorphism of the VDR gene in the studied Cuban patients.